A Sharia Economic Law Review of the Furniture Rotating Savings System in Rural Communities : Tinjauan Hukum Ekonomi Syariah Terhadap Sistem Arisan Furniture Di Masyarakat Pedesaan - Feby Nurjannah; Abdul Hanip; Sukaena fauziah; Ifan Ali Alfatani (Program Studi Hukum Ekonomi Syari'ah, 2026)
Arisan is one of the socio-economic activities that many people carry out as a means of saving, meeting household needs, obtaining business capital, and strengthening social relations between members. From an Islamic economic perspective, the practice of arisan must be carried out based on the principles of ta'awun (help), trust, justice, willingness, and transparency, and be free from elements of usury, gharar, maysir, fraud, and tyranny. This research aims to find out the practice of arisan furniture carried out by rural communities and analyze it based on Islamic law. The method used is qualitative research with a field research approach. Data was obtained through interviews and documentation of parties involved in social gathering activities. The results of the study show that arisan furniture helps people meet household needs that are difficult to buy in cash. In the review of sharia economic law, the practice uses the qard (loan) and al-bai' (buying and selling) contracts. The furniture arisan that was studied was considered legitimate because it met the elements of arisan and did not contain practices that were contrary to Islamic law. This study concludes that arisan can be accepted in the Islamic economy if it is managed in a trustworthy, fair, transparent manner, and based on a clear agreement. In order to remain in accordance with sharia principles, good recording, clarity of contracts, cost transparency, late rules, and a fair dispute resolution mechanism for all participants are needed.